2018
DOI: 10.1186/s13049-017-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different coagulation algorithms on the use of allogenic blood products and coagulation factors in severely injured trauma patients: a retrospective, multicentre, observational study

Abstract: Background: At the University Hospital Zurich (USZ) and the Cantonal Hospital of Lucerne (LUKS) an individualized goal-directed coagulation and transfusion algorithm was introduced and implemented before 2012 (Coagulation algorithm of the USZ: USZ-Alg; of the LUKS: LUKS-Alg). Main differences between both algorithms are: 1) A target haematocrit-range of 0.21-0.24 (USZ-Alg) vs. a lower haematocrit limit only (LUKS-Alg). 2) Blind coagulation-package in selected cases (LUKS-Alg only). 3) Factor XIII substitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The authors of the European Trauma Treatment Guidelines, for example, believe that education and adhering to coagulation protocols yield the greatest improvement in patient outcomes [7]. Other studies showed that the implementation of such coagulation algorithms indeed reduced patient mortality signi cantly [20,21]. Further, a user-centered design of the treatment protocols also had signi cant positive effects with seven times higher odds ratios of correctly treating a simulated bleeding case [13].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the European Trauma Treatment Guidelines, for example, believe that education and adhering to coagulation protocols yield the greatest improvement in patient outcomes [7]. Other studies showed that the implementation of such coagulation algorithms indeed reduced patient mortality signi cantly [20,21]. Further, a user-centered design of the treatment protocols also had signi cant positive effects with seven times higher odds ratios of correctly treating a simulated bleeding case [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it may also suggest different transfusion habits between both countries, especially, as transfusion habits in certain Swiss-level-one trauma centers changed markedly within the last decade [28]. Swiss transfusion rates probably dropped due to the implementation of a goal-directed coagulation algorithm, and increasing utilization of tranexamic acid and coagulation factor XIII [28,29].…”
Section: Despite Equal Injury Severity and A Comparable Amountmentioning
confidence: 99%
“…The principle goal of CFC-based treatment strategies is to reduce transfusion rates of allogeneic blood products and associated risks like anaphylactic reactions, transfusion related acute lung injury, multiorgan failure and severe infections 7 . The clinical effectiveness of CFCs in this context has been demonstrated in a large number of clinical trials and current scienti c rationale exists to support CFC repletion in patients with ongoing bleeding and con rmed coagulation factor de ciency 8,9,10 . By contrast there is certain paucity of high-quality evidence in favor of plasma when compared to CFC containing products, although plasma transfusion is still a widely accepted standard of trauma and non-trauma massive transfusion protocols (MTP) 11 .…”
Section: Introductionmentioning
confidence: 99%